Theoretical Analysis of Damaged Width & Instability Mechanism of Rib Pillar in Open-Pit Highwall Mining - Rui Wang; Shuai Yan; Jianbiao Bai; Zhiguo Chang; Tianhao Zhao (Advances in Civil Engineering)
To improve the resources’ recovery ratio and the economic benefits of open-pit mines, the development of highwall mining is used to exploit residual coal. The design of rib pillar, formed by excavation and mining activities in intact coal seams, is crucial to the overall stability and safety of the highwall mining operations. This paper focuses on the damage caused to rib pillars by the large deformation, occurring with the application of highwall mining in an open-pit in China. A mechanical model was established to investigate the damaged width of colinear rib pillars based on Hoek–Brown and Mohr–Coulomb failure criterion. The equations for calculating the damaged width of the rib pillar were obtained, respectively, by combining the Hoek–Brown failure criterion with the Mohr–Coulomb failure criterion. The failure mechanism for the width of the rib pillar and the factors affecting the colinear rib pillar were analyzed in detail. The results show that the application of the Hoek–Brown criterion has a unique advantage in analyzing the damaged width of the colinear rib pillars, in open-pit highwall mining. The instability mechanism and failure process of the rib pillars are described in combination with the limiting equilibrium method and the ratio of the elastic zone’s width to the width of the entire rib pillar.